Long-term neuropsychological sequelae, emotional wellbeing and quality of life in patients with acquired thrombotic thrombocytopenic purpura - Riva, Silvia (Haematologica, 2020)
Neurological symptoms related to microthrombosis are the hallmark of acute manifestations of acquired thrombotic thrombocytopenic purpura (TTP). Despite the achievement of hematological remission, patients may report persisting neurological impairment that affects their quality of life. To assess the long-term neuropsychological consequences of acute TTP, we recruited 35 acquired TTP patients (77% females, median age at onset 41 years, interquartile range: 35–48) regularly followed at our out-patient clinic of thrombotic microangiopathies in Milan (Italy) from December 2015 to October 2016. Patients underwent a psychological evaluation of memory and attentional functions, emotional wellbeing and health-related quality of life at least three months after their last acute TTP event (median 36 months, interquartile range: 17–54). During the psychological consultation, 17 patients (49%) referred persisting subjective neurological impairment in the frame of a remission phase, with at least one symptom as disorientation, loss of concentration, dizziness, lack of balance, headache and diplopia. Neuropsychological assessment revealed lower scores than the Italian general population pertaining to direct, indirect and deferred memory. A higher degree of impairment of memory domains was found in patients with neurological involvement at the time of presentation of the first acute TTP episode. Anxiety and depression were detected in seven (20%) and 15 (43%) patients, respectively. Health-related quality of life was lower than the Italian general population, with mental domains more impacted than physical domains (mean difference 58.43, 95% confidence interval: 71.49–45.37). Our study demonstrates compromised memory and attention functions, persisting anxiety/depression symptoms and a generally reduced quality of life in patients recovering from acute acquired TTP. New clinical strategies should be considered to improve these symptoms.